Multi-detector computer tomography as effective method for Crohn's disease diagnostics - A. A. Tikhonov; A. V. Gorinov; I. V. Zarodnyuk; I. L. Khalif; Ye. S. Korolevsky (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Improvement of diagnostics and efficacy of radiological methods of investigation by technique computer-tomography (CT) enterography at inflammatory bowel diseases.Material and methods. Original investigation was based on the data of comprehensive clinical and instrumental investigation of 111 patients with suspected Crohn's disease (CD). The set of tests included colonoscopy, abdominal US, CT-enterography, X-ray investigation of small intestine. Signs of CD were obtained by CT-enterography in 62 patients (55,9%), in all of these cases it was possible to establish localization of process, to estimate its spread and reveal complications.Results. Data of roentgenological and CT investigation comparative analysis were similar. Thus, CT-enterography technique of can be regarded either as alternative to X-ray investigation of the small intestine at CD diagnostics or important addition to diagnostic algorithm for this group of patients.